Relevancy education regulation and the implementation in Indonesia (analysis of educational reform) - Trinova, Zulvia; Khasanah, Khasanah; Heryani, Ani (International research journal of management, IT and social sciences, 2021)
Finding data to discuss the relevance of education regulations and their implementation in Indonesia through an analysis of education reform is the essence of this study. So, there are several publications that we use as literature to answer this problem. These publications include ResearchGate, ERIC, Google Books, and several relevant online kinds of literature that we refer to in this study after we found the data and then investigated it by involving a simple study system such as a data coding system and in-depth evaluation. Moreover, until we got the data findings, interpretation answered this problem with high validity and reliability principles. We focus on data published ten years ago so that the data is more up-to-date. Based on the study and discussion of the results, we can say that the results are relevant to the realization of education related to the set of rules governing the implementation of the education system, which includes the goals of education and how to achieve these goals. However, in its application, it still encounters obstacles that are still being searched for following the regulation’s mandate.